Website Vulnerability Analysis of AB and XY Office in East Java - Muchammad Zaidan; Febyola Noeraini; Zamah Sari; Denar Regata Akbi (Jurnal Ilmiah Teknik Elektro Komputer dan Informatika, 2023)
Study this aim for analyze and identify vulnerability existing security on AB and XY Service Websites in East Java. Contribution study this is give more understanding deep about type vulnerability specific security and its impact to field website security. Method research used involve data scanning, analysis vulnerabilities, and Brute Force experiments. A total of 2 samples of AB and XY Service Websites were analyzed For identify existing vulnerabilities the data. However so, necessary noted that method study this own a number of limitations. First, size sample used possible limited to AB and XY Service Websites in East Java only, so generalization results study against other websites needs done with be careful. Second, analysis statistics used only covers analysis descriptive, so study this not yet investigate linkages between existing variables. Although thus, results study show exists necessary weaknesses and vulnerabilities corrected on AB and XY Service Websites. A number of findings covers problem website configuration and handling vulnerability that is not adequate. With highlight specific susceptibility, research this give more understanding deep about threat security faced by AB and XY Service Websites. In context field website security, research this own implication important. With understand existing vulnerabilities on AB and XY Service Websites, steps repair proper security can take for protect sensitive data and improve protection security in a manner whole. Kindly whole, research this identify and analyze vulnerability security on AB and XY Service Websites, as well give more understanding Specific about type existing vulnerabilities. Although there are limitations in method study this is the result still give valuable insight in field website security and can become base for repair more security effective and more data protection on both the AB and XY Service Websites.